Historical structure of time in information theory - Drożdż, Michał (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2005)
Carl von Weizsäcker analyzes the information concept in the framework of his own philosophy. He emphasizes, on the one hand, the irreversibility inherent in the time structure and, on the other hand, the dependence of information on temporal relations. In his view, information constitutes an abstract, albeit real, element of the world related to the form, structure, and order. Its quantitative and dynamical character assimilates it to matter and energy. Information does not exist outside material processes and human consciousness. Its dynamical aspect is strictly connected with communication, and evolutionary and entropic processes. In Weizsäcker's view, information becomes a philosophical concept. His approach hardly could be regarded as a full theory of time and information; it is rather an attempt at grasping their mutual dependencies and meaning.